Garbagriha at the Vyankatesh Balaji Temple - Ghosh, Ayan (2023)
Entrance to the garbagriha at Vyankatesh Balaji Temple. The doorway has niches on either side. On the left is Lord Hanuman, wearing a crown, armed with a bow and arrow, and praying with folded hands. On the right is Lord Ganesha, also wearing a crown. Both idols, and that of Lord Balaji in the garbagriha, are made of marble quarried from Rajasthan.